2010
DOI: 10.1111/j.1540-8167.2010.01844.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in the HCN4 Gene Causes Symptomatic Sinus Bradycardia in Moroccan Jews

Abstract: Objectives-To conduct a clinical, genetic and functional analysis of three unrelated families with familial sinus bradycardia (FSB).Background-Mutations in the hyperpolarization-activated nucleotide-gated channel (HCN4) are known to be associated with FSB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 32 publications
(69 reference statements)
0
59
0
Order By: Relevance
“…Together, the loss-offunction effects of the shifts in the voltage dependence of 1795insD 41 ± 1** 70 ± 1** 124 ± 3** 54 47 ± 1 77 ± 2 141 ± 3 40 Van den Berg et al [12] In HCN4 G480R 32 ± 8* 49 ± 12* 101 ± 21* 7 55 ± 9 73 ± 11 126 ± 17 8 Nof et al [13] A485V 37 ± 3* 58 ± 6* 117 ± 27 14 49 ± 11 77 ± 12 140 ± 33 5 Laish-Farkash et al [14] 695X 36 ± 6* 56 ± 5* 131 ± 17 7 47 ± 6 72 ± 10 157 ± 26 6 Schweizer et al [15] Minimum (Min), average (Avg), and maximum (Max) heart rate (HR) obtained with 24-hour Holter recording. Data are mean ± SEM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, the loss-offunction effects of the shifts in the voltage dependence of 1795insD 41 ± 1** 70 ± 1** 124 ± 3** 54 47 ± 1 77 ± 2 141 ± 3 40 Van den Berg et al [12] In HCN4 G480R 32 ± 8* 49 ± 12* 101 ± 21* 7 55 ± 9 73 ± 11 126 ± 17 8 Nof et al [13] A485V 37 ± 3* 58 ± 6* 117 ± 27 14 49 ± 11 77 ± 12 140 ± 33 5 Laish-Farkash et al [14] 695X 36 ± 6* 56 ± 5* 131 ± 17 7 47 ± 6 72 ± 10 157 ± 26 6 Schweizer et al [15] Minimum (Min), average (Avg), and maximum (Max) heart rate (HR) obtained with 24-hour Holter recording. Data are mean ± SEM.…”
Section: Resultsmentioning
confidence: 99%
“…Holter recording in 1795insD patients revealed sinus bradycardia with an ≈11% decrease in minimum, average, and maximum heart rate [12], as detailed in Table 1, which also shows the bradycardic effect of some typical HCN4 mutations [13][14][15] for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Average resting heart rate (mean ± SEM) was 49 ± 12 bpm (range 36-72 bpm) in the 7 mutation carriers vs. 73 ± 11 bpm (range 55-89 bpm) in the 8 non-affected family members. Similarly, Laish-Farkash et al [10] reported on three families of Moroccan Jewish decent with the A485V mutation. The average heart rate of 14 mutation carriers was 58 ± 6 bpm (range 49-70 bpm), whereas that of 5 non-carriers was 77 ± 12 bpm (range 59-91 bpm).…”
Section: Introductionmentioning
confidence: 99%
“…In a single German family with the 695X mutation, Schweizer et al [11] observed an average heart rate of 56 ± 5 bpm (range 47-61 bpm) in 7 mutation carriers vs. 72 ± 10 bpm (range 58-86 bpm) in 6 non-carriers. The clinical data of Nof et al [9], Laish-Farkash et al [10], and Schweizer et al [11] are not limited to the average heart rate. They also reported the minimum and maximum heart rate obtained with 24-hour Holter recording.…”
Section: Introductionmentioning
confidence: 99%
“…We recently 38 identified 2 families with symptomatic bradycardia. Affected members presented with a history of presyncope, except for one subject who had a poorly documented event of loss of consciousness with apparent cardiopulmonary arrest, which resolved following basic CPR; he recovered without defibrillation.…”
Section: Hcn4mentioning
confidence: 99%